EFFECT OF FOLIAR APPLICATION OF NITROGEN AND BORON ON THE YIELD OF TOMATO (LYCOPERSICON ESCULENTUM MILL.) (International Journal of Food and Nutritional Sciences, 2021)
The present investigation entitled “Effect of Nutrient application of Nitrogen and Boron on the Yield of Tomato (Lycopersicon esculentum Mill.)’’ was conducted at the experimental farm of the faculty of Agricultural Sciences and Allied Industries, Rama University, Mandhana, Kanpur (U.P.) during 2017-18. The experiment was laid out in randomized block design (RBD) with three replications comprising of 16 treatment combinations. The treatments were Nitrogen (0 %, 0.10 %, 0.15 % and 0.20 %) and Boron (0 %, 0.15 %, 0.20 % and 0.25 %). Seeds of Azad T-9’ were sown in the nursery on 15th Sep.2017 and transplanting was done on 22th Oct.,2017 and result, N3 (0.20%) and B3 (0.25%) produced maximum significant values of every yield attributes of tomato. So, it is advised to research workers and vegetable growers of Central Uttar Pradesh that for obtaining optimum yield spraying with 0.20% nitrogen and 0.25% boron is recommended.